Global policy approaches to combat early childhood caries: a scoping review with evidence map - Lydia, Nagarajan; Imran, Mohammed; Atique, Sundus; Bahammam, Hammam Ahmed; Moothedath, Muhamood; Habibullah, Mohammed Ali; Kolarkodi, Shaul Hameed (Frontiers in Oral Health, 2025)
BackgroundEarly Childhood Caries (ECC) is a major global public health concern disproportionately affecting young children, particularly in low-resource settings. Although several clinical and community-based interventions have been implemented, the contribution of policy measures in addressing ECC remains insufficiently explored at the global level.ObjectiveThis scoping review aimed to identify, describe, and map policy approaches adopted across countries for the prevention and management of ECC.MethodsThe review followed the Arksey and O'Malley framework and adhered to the PRISMA-ScR guidelines. A comprehensive literature search was conducted in PubMed, CINAHL, Web of Science, and Google Scholar for studies published between 2014 and 2024. Eligible studies focusing on ECC-related policies were included and analyzed thematically.ResultsA total of 28 articles met the inclusion criteria. The identified policy approaches were categorized into three major domains: preventive, regulatory, and integrative strategies. These policies were implemented across high-, middle-, and low-income countries, with the majority originating from high-income settings. Implementation channels included schools, health systems, and mass media campaigns. Major gaps identified were limited policy initiatives in low-income countries, weak integration with primary healthcare, and inadequate monitoring and evaluation frameworks.ConclusionWhile progress has been made in ECC policy development globally, significant disparities persist in implementation and impact. The findings highlight the urgent need for comprehensive, equity-oriented, and system-integrated policy interventions to effectively prevent and control ECC worldwide.Systematic Review RegistrationThe review protocol is registered at the Open Science Framework database under the Registration https://doi.org/10.17605/OSFIO/2VMEK.